A measurement model of technological pedagogical content knowledge (TPACK) in Indonesian senior mathematics teachers' scenario. (October 2020) - Yanuarto, W N; Maat, S M; Husnin, H
Abstract: The TPACK is one of the primary knowledge for teachers understanding technology in the era of the industrial revolution 4.0. In education, teaching technology in the classroom can apply by looking at the TPACK stages teachers have. Teachers who have high stages in TPACK will facilitate their steps and movements in exploring technology in the classroom. This study aims to validate the TPACK measurement model, which consists of 30 items. A quantitative method of the cross-sectional survey is applied in this study. We used the questionnaire for gaining the data. TPACK instruments were distributed to 235 respondents. The analysis of this TPACK measurement model testing uses exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). All constructs revealed acceptable internal consistency reliability. A good model fit found for measurement models of TPACK using several fit index tests like CMINDF, GFI, CFI, TLI, and RMSEA. The findings showed that all fit indices criteria were fulfilled. It is concluded that the TPACK measurement model pictures the TPACK level of the senior mathematics teachers in the Indonesian scenario.